Discrete wavelet transform based approach for current transformer saturation problem [Akim transformatörleri̇ni̇n doyma sorunlari üzeri̇ne ayrik dalgacik tabanli bi̇r yöntem] - (:unkn) unknown (My University, 2009)
This work is about the possible effects of protection devices and schemes during current transformer saturation. If current transformer specifications are not selected properly, saturation may occur and affect relay response or even fail to trip. Hence, the performance of the protection devices such as differential and impedance relays is mainly based on the operating condition of the current transformers. An accurate knowledge of current signal is essential for protection devices. In this paper, a different approach is represented for current transformer saturation problem. The proposed technique is based on the discrete wavelet transform. The energy levels of the detail coefficients after the transformation present distinctive features during current transformer saturation. ©2009 IEEE.